Palliative care as an emerging role for respiratory health professionals: Findings from a cross-sectional, exploratory Canadian survey. - Goodridge, Donna; Peters, Jaimie (Canadian Journal of Respiratory Therapy, 2019)
Introduction: Respiratory Health Professionals (RHPs) with specialty training in the management of asthma and COPD, often care for patients with advanced respiratory disease, who have less access to palliative care than patients with similar disease burden. The aims of this study were to: (i) explore the current and desired roles of RHPs in terms of palliative care and (ii) examine barriers to discussions with patients about palliative care. Methods: An online survey addressing the aims of this study was developed and pilot tested. The survey was distributed nationally using the database of the Lung Association's RESPTREC respiratory educator training program. Descriptive statistics were performed. Results: A total of 123 completed surveys were returned, with respiratory therapists comprising the largest group of respondents. The majority indicated that end-of-life care was less than optimal for patients with advanced respiratory illnesses and agreed that palliative care should be a role of RHPs. Patientand family-related barriers to having end-of-life discussions included: difficulty accepting prognosis, limitations and complications, and lack of capacity. For providers, the most important barriers were: lack of training, uncertainty about prognosis, and lack of time. The health care system barriers of concern were increasing demand for palliative care services and limited accessibility of palliative care for those with advanced respiratory diseases and difficulties in accurate prognostication for these conditions. Discussion: Incorporating a more defined role in palliative care was generally seen as a desirable evolution of the RHP role. A number of strategies to mitigate identified barriers to discussions with the patient are described. Better alignment of the services required with the needs of patients with advanced respiratory disease can be addressed in a number of ways. Conclusions: As RHP roles continue to evolve, consideration should be given to the ways in which RHPs can contribute to improving the quality of care for patients with advanced respiratory disease. Building collaborations with RHPs, palliative care, and other existing health programs can ensure high quality of care. Creating and taking advantage of learning opportunities to build skills and comfort in using a palliative approach will benefit respiratory patients.